2015
DOI: 10.1162/jocn_a_00745
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Agency in Observed Actions: Evidence for N1 Suppression of Tones Caused by Self-made and Observed Actions

Abstract: Abstract■ Every day we make attributions about how our actions and the actions of others cause consequences in the world around us. It is unknown whether we use the same implicit process in attributing causality when observing othersʼ actions as we do when making our own. The aim of this research was to investigate the neural processes involved in the implicit sense of agency we form between actions and effects, for both our own actions and when watching othersʼ actions. Using an interval estimation paradigm t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 71 publications
4
47
1
Order By: Relevance
“…The paradigm used in the present study required button presses at regular intervals so that observers might have been able to predict the onset of the observed movement to some extent. The analysis of preaction potentials in the present study did not, however, reveal strong evidence of predictive mechanisms in observers, and the negativity preceding the observed action might also be interpreted as a contingent negative variability reflecting predictable stimuli (Kilner et al, 2004;Poonian et al, 2015). Moreover, the correlations between preaction potentials and the reduction of the N1 amplitude were far from reaching significance in both experimental groups (for opposite findings for active button presses, see Ford et al, 2014), as was the correlation between the variability of the timing of the observed button press and the N1 amplitude in observers.…”
Section: N1 Componentcontrasting
confidence: 96%
See 2 more Smart Citations
“…The paradigm used in the present study required button presses at regular intervals so that observers might have been able to predict the onset of the observed movement to some extent. The analysis of preaction potentials in the present study did not, however, reveal strong evidence of predictive mechanisms in observers, and the negativity preceding the observed action might also be interpreted as a contingent negative variability reflecting predictable stimuli (Kilner et al, 2004;Poonian et al, 2015). Moreover, the correlations between preaction potentials and the reduction of the N1 amplitude were far from reaching significance in both experimental groups (for opposite findings for active button presses, see Ford et al, 2014), as was the correlation between the variability of the timing of the observed button press and the N1 amplitude in observers.…”
Section: N1 Componentcontrasting
confidence: 96%
“…This interpretation would be in line with the hypothesis that forward models might play a role also in action observation based on a simulation of the motor command (Wolpert et al, 2003). Similar predictive mechanisms for both action execution and observation have been recently suggested in an EEG study by Poonian et al (2015), in which an N1 suppression for processing the auditory consequences of observed actions was found. Poonian and colleagues, however, applied an interval estimation task to investigate intentional binding, in which a tone followed a self-performed or observed action after a variable delay of more than 500 up to 1,500 ms.…”
Section: N1 Componentsupporting
confidence: 87%
See 1 more Smart Citation
“…The N1 event-related potential is EFFORT DISRUPTS IMPLICIT AGENCY 31 suppressed in response to events that the participant themselves has caused (Caspar et al, 2016;Poonian, McFadyen, Ogden & Cunnington, 2015). This suppression is thought to index sense of agency due to top-down motor predictions causing a suppression of the processing of the effects of actions (Gentsch, Kathmann & Schutz-Bosbach, 2012).…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…A quite different way of conceptualizing temporal binding has emerged in the context of some more recent studies that have demonstrated instances of temporal binding also occurring outside of the context of voluntary action, for instance when participants passively observed another person's button press followed by a tone (Poonian, McFadyen, Ogden, & Cunnington, 2015), when an experimenter pressed down the participant's finger to initiate the tone (Borhani, Beck, & Haggard, 2017; see also Buehner, 2015), or when the button was simply depressed by a machine (Buehner, 2012). It has been hypothesized that instances of temporal binding such as this are a top‐down effect on perception reflecting a belief in a cause–effect relation between the two observed events.…”
Section: Introductionmentioning
confidence: 99%